SIMULATION OF EFFECTS OF GRAIN DISTRIBUTION MORPHOLOGY ON FATIGUE BEHAVIOR OF SHORT CRACKS AT WELD TOE (MT) - HU Ke; WEI GuoQian; YAN MengYu; FENG ZiBin; LI AHu (Jixie qiangdu)
Fatigue cracks of the welded structure often initiate at the weld toe. Under the complex metallurgical-physical process, the grain sizes and their distribution morphology at the weld toe site show obvious variation. In order to investigate the influence of grain distribution morphology on the fatigue behavior of the weld toe short cracks, metallographic tests were carried out for different areas of the weld toe for the cruciform joint specimen to obtain the average grain sizes of the coarse-grain region and the fine-grain region. Two-dimensional representative volume element（RVE） models considering grain distribution morphology were constructed. Based on FIP parameters and McDowell model, the nucleation and fatigue propagation behavior of the weld toe short cracks with different grain distribution morphology were simulated. The results showed that grain size and orientation are important factors influencing the nucleation behavior of the weld toe short cracks. The grain distribution morphology has little effect on the early behavior of short cracks, but the effect is gradually significant with the cracks propagating to a certain threshold length. In general, the fine-to-coarse grain transition mode can reduce the growth rate of short cracks.